Enhanced photo-assisted ethanol electro-oxidation activity by using broadband visible light absorption of a graphitic C3N4/BiOI carrier. Issue 2 (4th December 2018) - Hu, Jiayue; Zhai, Chunyang; Gao, Haifeng; Zeng, Lixi; Du, Yukou; Zhu, Mingshan
Abstract : A 2D/2D g-C3 N4 /BiOI heterojunction was used as a broad light harvesting support for the enhancement (16.9 times) of ethanol electro-oxidation under visible light irradiation. Abstract : Fuel cells have been recognized as promising next generation energy conversion devices. Recently, using semiconductors to improve the performance of fuel cell reactions under light irradiation has received increasing attention. In this paper, we used long-wavelength-absorption bismuth oxyiodide (BiOI) nanosheets coupled with graphite-like carbon nitride (g-C3 N4 ) nanosheets to form a 2D/2D composite. This 2D/2D heterojunction has a broad light harvesting ability in the visible light region, which provides an advantage for the unitization of solar energy. By decorating with Pt nanoparticles, the as-synthesized Pt/g-C3 N4 /BiOI electrode shows a 16.9 times enhanced catalytic activity under visible light (>420 nm) illumination compared to that of the conventional electrocatalytic oxidation reaction (dark conditions). Even using 600 ± 15 nm red light irradiation, the mass activity of Pt/g-C3 N4 /BiOI for the ethanol oxidation reaction reaches 53.1 mA mgPt −1 . Furthermore, the stability of the as-prepared Pt/g-C3 N4 /BiOI were also improved by using light illumination. These results provide a model for the construction of 2D/2D heterostructures for solar light-enhanced electrocatalysis in fuel cells using their broad absorption properties.